2020
DOI: 10.31234/osf.io/9v78y
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Psychological Distress Experiences of Nigerians Amid Covid-19 Pandemic

Abstract: This study examined the psychological distress experience of Nigerians amid COVID-19 pandemic. From March 20, 2020 to April 12, 2020, this descriptive survey used a snowballing sampling technique to select 502-Nigerian with an online semi-structured questionnaire containing Impact of Event Scale-Revised, GAD-7, Patient Health Questionnaire and Insomnia Severity Index. Gender had insignificant difference in the level of insomnia (χ2=04.93; df=3; p>0.05), however, 20.8% of males had sub-threshold of insom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Obviously, these negative effects have caused some psychological impacts -the prevalence of insomnia, depression and posttraumatic stress symptoms among Nigerians during COVID-19 pandemic [53]; including mental and physical stress among health practitioners thus leading to temporary separation from families, stigma and the pain of losing patient's and colleagues [23]. The survivals might experience social stigma from the society [14]; fear of being stigmatised could have prevented people with suspected cases of the virus from coming out voluntarily for testing [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obviously, these negative effects have caused some psychological impacts -the prevalence of insomnia, depression and posttraumatic stress symptoms among Nigerians during COVID-19 pandemic [53]; including mental and physical stress among health practitioners thus leading to temporary separation from families, stigma and the pain of losing patient's and colleagues [23]. The survivals might experience social stigma from the society [14]; fear of being stigmatised could have prevented people with suspected cases of the virus from coming out voluntarily for testing [51].…”
Section: Discussionmentioning
confidence: 99%
“…Even, many of them have acquired the virus and some have lost their lives [23]; leading to a global health crisis, particularly to handle critically ill patients [52]. Moreover, the experience of psychological impacts such as the prevalence of insomnia, depression and posttraumatic stress symptoms among Nigerians during COVID-19 pandemic have been reported [53].…”
Section: Situation Report Of Covid-19 Pandemic In Nigeriamentioning
confidence: 99%
“…The desire to understand the impact of the Covid-19 on people's social relationships and mental health as well as its influence on life satisfaction has led to the conduct of many studies among different categories of people in several countries of the world (Wang, et al, 2019;Fardin, 2020;Otu et al, 2020;Zhang & Ma, 2020;Blake, et al, 2020;Bukuluki, et al, 2020;Dai, et al, 2020;UCL, 2020;White & Boor, 2020;Briggs & Numbere, 2020;Olaseni, et al, 2020). For instance, examined the unprecedented disruption of lives and work: health, distress, and life satisfaction of working adults in China one month into the Covid-19 outbreak.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the severity of the disease in participants' city predicted their life satisfaction. Also, Olaseni et al (2020) reported the psychological distress experienced by Nigerians amid the Covid-19 pandemic. The result of the study revealed that Nigerians generally experienced various degrees of distress during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…4 The feeling of loneliness, due to reduced social interactions is a challenge for several psychological disorders such as; anxiety, drug abuse, insomnia, major depression etc. 5 Fear of losing livelihood due to isolation, constant sense of insecurity for oneself and loved once, affect in the availability of basic supplies can add to change in an individual's mental health status. 6 Authors in China have found insomnia is highly prevalent and associated with COVID-19.…”
mentioning
confidence: 99%